RSS Statistics in Sports Section`s Olympic prediction competition 2024 - Powell, B. (Department of Mathmatics at the University of York, 2025)
In this report we analyze and discuss the problem of predicting the Olympics medals table. The work presented here is informed by the ideas and findings of entrants to a Royal Statistical Society prediction competition, who competed to predict the medals table for the 2024 Olympic Games in Paris.